Genetic and Biochemical Characterization of 2-Chloro-5-Nitrophenol Degradation in a Newly Isolated Bacterium, Cupriavidus sp. Strain CNP-8 - Min, Jun; Chen, Weiwei; Wang, Jinpei; Hu, Xiaoke (Frontiers in Microbiology, 2017)
Compound 2-chloro-5-nitrophenol (2C5NP) is a typical chlorinated nitroaromatic pollutant. To date, the bacteria with the ability to degrade 2C5NP are rare, and the molecular mechanism of 2C5NP degradation remains unknown. In this study, Cupriavidus sp. strain CNP-8 utilizing 2-chloro-5-nitrophenol (2C5NP) and meta-nitrophenol (MNP) via partial reductive pathways was isolated from pesticide-contaminated soil. Biodegradation kinetic analysis indicated that 2C5NP degradation by this strain was concentration dependent, with a maximum specific degradation rate of 21.2± 2.3 μM h-1. Transcriptional analysis showed that the mnp genes are up-regulated in both 2C5NP- and MNP-induced strain CNP-8. Two Mnp proteins were purified to homogeneity by Ni-NTA affinity chromatography. In addition to catalyzing the reduction of MNP, MnpA, a NADPH-dependent nitroreductase, also catalyzes the partial reduction of 2C5NP to 2-chloro-5-hydroxylaminophenol via 2-chloro-5-nitrosophenol, which was firstly identified as an intermediate of 2C5NP catabolism. MnpC, an aminohydroquinone dioxygenase, is likely responsible for the ring-cleavage reaction of 2C5NP degradation. Gene knockout and complementation indicated that mnpA is necessary for both 2C5NP and MNP catabolism. To our knowledge, strain CNP-8 is the second 2C5NP-utilizing bacterium, and this is the first report of the molecular mechanism of microbial 2C5NP degradation.